Meningkatkan Motivasi Belajar Melalui Model Pembelajaran Problem Based Learning (PBL) dengan Media Canva Bagi Siswa Fase F SMA Negeri 1 Prambanan Tahun Pelajaran 2024/2025 - Christina Heti Tyas Widayanti; Anselmus Yata Mones; Maria Margaretha Dwilinda (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to determine whether the use of the PBL learning model with Canva media can increase student learning motivation, which is indicated by increased interest, active participation, and enthusiasm of students in participating in learning activities through the PBL model in students at SMA Negeri 1 Prambanan. This type of research is classroom action research with research steps, namely planning, implementation, observation, and reflection in each cycle. This study consists of two cycles. The research location is at SMA Negeri 1 Prambanan Sleman in Phase F students. Data collection techniques are observation, questionnaires and interviews. The results of the study in cycle 1 can be concluded that student motivation gets the criteria "good". This can be used as one of the benchmarks that learning activities with Problem Based Learning are good but need to be improved in asking questions to analyze critically, courage in conveying information, cooperation in groups, courage in expressing opinions and explaining reasons that support their thoughts. The results of the study in cycle II can be concluded that student activities get the criteria "very good". This can be used as one of the benchmarks that Problem Based Learning learning activities with Canva media are good and have increased compared to the first cycle. Based on the data obtained from the tests given to students in cycle 1, it was found that 66.6% of students were proficient and 33.3% of students were competent through the Problem Based Learning method. The desired achievement from this learning model in the second cycle is proficient 40%, proficient 50%, decent 10% and not yet developed 0%. The percentage of proficient students increased with the tests conducted in the second cycle, there was an increase in the percentage of proficient students. In cycle 1, the learning achievement was proficient 16.6% and proficient 83.3%. While in the second cycle, students who were proficient were 66.6% and proficient 33.3%. Looking at the learning outcomes in cycles 1 and 2, it can be seen that problem based learning was successful in improving student learning outcomes.